Sie sind auf Seite 1von 24

# FEngO

Foundation Degree

Mathematics

Pre-Course
Study Package

## Name: …………………………… Service No: …………………

MATHEMATICS PRE-COURSE STUDY PACKAGE

## This package has been designed so that all students on the

FEngO Foundation Degree course have the opportunity to practice
basic algebraic manipulation before arriving at DCAE Cosford. This
will enable all students to achieve a common entry level for the
start of the mathematics module.
The nine exercises are to be completed and handed in on the first
day of the course. On the first mathematics lesson a diagnostic
test on these topics will be set. The outcome of this test will be
used to assess areas of potential strengths and weaknesses of
each individual student. These can then be addressed during the
20 period Maths lead-in course.

2
TRANSPOSITION OF FORMULA

## The process of rearranging a formula so that one of the other

symbols becomes the subject is called transposing the formula.

Example 1

## Transpose the formula F = ma to make a the subject

F ma
Divide both sides by m =
m m

F F
=a or a=
m m

Example 2

## Subtract c from both sides y − c = mx = c − c

y − c = mx

y − c mx
Divide both sides by m =
m m

y −c y −c
=x or x=
m m

3
Example 3

w( H − h)
Transpose the formula Q= to make T the subject
T−t

w( H − h )
Multiply both sides by T − t Q( T − t ) = × (T − t )
T−t

Q( T − t ) = w ( H − h )

Q( T − t ) w ( H − h )
Divide both sides by Q =
Q Q

w( H − h)
T−t=
Q

w( H − h )
Add t to both sides T−t+t= +t
Q

w( H − h)
T= +t
Q

w( H − h )
Subtract from both sides
Q

w( H − h) w( H − h ) w( H − h )
T− = +t−
Q Q Q

w( H − h)
T− =t
Q

w( H − h)
t=T−
Q

4
Example 4

ab
Transpose the formula y= to make a the subject
a−b

ab
Multiply both sides by a − b y (a − b ) = (a − b )
a−b

y (a − b ) = ab

## Group all the terms containing an a

on the LHS and all other terms on ay − ab = by
the RHS.

## Factorise the LHS a( y − b ) = by

a( y − b ) by
Divide both sides by ( y − b ) =
(y − b) y − b

by
a=
y −b

Example 5

subject

## Add 1 to both sides (n − 1) + 1 = t + 1

n = t +1

5
Example 6

b( x − b )
Transpose the formula d= to make x the
c
subject

b( x − b )
Square both sides d2 =
c

b( x − b )
Multiply both sides by c cd 2 = ×c
c

cd 2 = b( x − b )

cd 2 b( x − b )
Divide both sides by b =
b b

cd 2
=x−b
b

cd 2
Add b to both sides +b=x−b+b
b

cd 2
+b=x
b

cd 2
Or x= +b
b

6
EXERCISE 1

## 5) v 2 = 2gh for h 6) I=PRT for R

a E
7) x = for y 8) I = for R
y R

u RT
9) x = for u 10) P = for T
a V

1 2 3 1 1 1 1
11) = + for b 12) = + + for R2
a b c R R1 R 2 R 3

PLAN πd 2 h
13) H = for L 14) V = for h
33000 4

## 17) n = p + cr for r 18) y = ax + b for x

x
19) y = + 17 for x 20) H = S + qL for q
5

## 21) a = b − cx for x 22) D = B − 1 ⋅ 28d for d

2R E
23) V = for r 24) C = for E
R−r R+r

## 25) S = πr (r + h ) for h 26) H = wS(T − t ) for T

7
N−n 12(D − d )
27) C = for N 28) T = for d
2p L

2R S(C − F)
29) V = for R 30) P = for C
R−r C

## 31) V = 2gh for h 32) w = k d for d

L W
33) t = 2π for L 34) t = 2π for f
g gf

mv 2 x
35) P − mg = for m 36) Z = for x
r x+y

3n + 2 3
37) k = for n 38) a = for t
n +1 4t + 5

⎛ 1 1⎞ 2(S − an )
39) v 2 = 2k ⎜ − ⎟ for x 40) d = for a
⎝x a⎠ n (n − 1)

dh
41) c = 2 2hr − h 2 for r 42) x = for d
D−d

D f +p W(v − u)
43) = for f 44) F = for t
d f −p gt

1− t2 R−H
45) y = for t 46) T = 2π for R
1+ t2 g

3n + 2 ab
47) k = for n 48) y = for b
n +1 a−b

b a 2 − b2
49) a = for b 50) x = for y
b+c ay

8
LINEAR EQUATIONS

## A linear equation is an equation that contains only one unknown.

For example;
1) 7x + 3 = 5x + 17
2) 2(3x + 7) = 16
3) 3( x + 4) − 5( x − 1) = 19
x 3 3x
4) + = −2
4 5 2
x − 4 2x − 1
5) − =4
3 2
5 4
6) =
2x + 5 x + 2

## The method used to solve linear equations is exactly the same as

for transposition of formula.

Example 1 Solve 7x + 3 = 5x + 17

## Rearrange by subtracting 5x and 3 from both sides so that the LHS

contains all the x terms and the RHS all the non x terms.

7 x + 3 − 5x − 3 = 5x + 17 − 5x − 3
2x =14
14
x= x=7
2

## Removing the bracket 6 x + 14 = 16

Subtract 14 from both sides 6 x + 14 − 14 = 16 − 14
6x = 2
6x 2
Dive both sides by 6 =
6 6

1
Therefore x=
3

9
Example 3 Solve 3( x + 4) − 5( x − 1) = 19

## Removing the brackets 3x + 12 − 5x + 5 = 19

− 2 x + 17 = 19

Re-arranging 19-17= - 2x
Therefore 2= -2x

x = -1

x 3 3x
Example 4 Solve + = −2
4 5 2

x 3 3x
Multiply by the LCD 20 × 20 + × 20 = × 20 − 2 × 20
4 5 2

5x + 12 = 30x − 40

12 + 40 = 30x − 5x

52 = 25x

52 2
x= x=2
25 25

x − 4 2x − 1
Example 5 Solve − =4
3 2

⎛ x − 4⎞ ⎛ 2x − 1 ⎞
Multiply by the LCD 6 ⎜ ⎟×6 −⎜ ⎟×6 = 4×6
⎝ 3 ⎠ ⎝ 2 ⎠

2( x − 4) − 3( 2 x − 1) = 24

2 x − 8 − 6 x + 3 = 24

− 8 + 3 − 24 = 6 x − 2 x

1
− 29 = 4 x x = −7
4
10
5 4
Example 6 Solve =
2x + 5 x + 2

## Multiply both sides by ( 2 x + 5)( x + 2)

5 4
(2 x + 5)( x + 2) × = (2 x + 5)( x + 2) ×
(2 x + 5) x+2

5( x + 2) = 4( 2 x + 5)

5x + 10 = 8x + 20

10 − 20 = 8x − 5x

− 10 = 3x

− 10
x=
3

1
x = −3
3

## Exercise 2 Solve the following linear equations.

1) 6 x − 7 = 17 2) 14 − 3x = 8

3) 6 x + 11 = 25 − x 4) 0 ⋅ 3x = 1 ⋅ 8

5) 1 ⋅ 2 x − 0 ⋅ 8 = 0 ⋅ 8x + 1 ⋅ 2 6) 2( x + 1) = 8

7) 3( x − 1) − 4( 2x + 3) = 14 8) 5( x + 2) − 3( x − 5) = 29

## 9) 3x = 5(9 − x ) 10) 4( x − 5) = 7 − 5(3 − 2 x )

11
x x x x x 5
11) − =2 12) + + =
5 3 3 4 5 6

x x x 3 2x
13) + +3=2+ 14) 3x + =2+
2 3 6 4 3

3 4 3
15) =3 16) y− y=2
x 7 5

1 1 7 x +3 x −3
17) + = 18) − =2
3x 4 x 20 4 5

2 x x − 6 3x 3 2 x − 3 4 − 5x
19) − − = 20) =
15 12 20 2 4 3

3− y y 3x − 5
21) = 22) x − 5 =
4 3 6

x−2 3 2
23) =3 24) = 11
x −3 x −1 x − 5

3 4 3 5
25) = 26) =
x−2 x+4 2 x + 7 3( x − 2)

x 3x − 7 x − 2 4 x − 1 3x − 1 5 − 2 x
27) − = 28) − =
3 5 6 3 2 4

3x − 5 9 − 2 x x 2x − 5
29) − =0 30) − =0
4 3 3 2

4x − 5 2x − 1 ( x − 3) 3( x − 1) 2
31) − =x 32) + =1
2 6 12 8 3

2( 4 − x ) 2( x + 5) 2 3( 2 x + 3) 5(5x + 3) 2
33) − =4 34) − =8
9 3 3 7 6 3

12
(3x + 1) 3( 4 − x ) 4 5x + 2 7 x − 5 1
35) + =1 36) + =6
5 3 15 3 4 4

3( x − 2) 4( x − 7 ) 2 5( 2 x + 1) 2( 4 x + 1) 2
37) + =1 38) − = 11
4 3 3 3 5 3

## 7(3 − x ) 4(5 + x ) 1 5(3x − 4) 2(3 − 2 x )

39) − = 20 40) − = 22
4 3 6 2 5

13
SIMUTANEOUS EQUATIONS

## Consider the following two pairs of equations

1) 3x + 4 y = 11 and x + 7 y = 15

2) 3x + 4 y = 26 and 4 x − 3y = 18

## Example 1 Solve the equations:

3x + 4y = 11 ……. (1)
and x + 7y = 15 ……. (2)

## The first objective is to make the coefficients of either x or y to be

the same. To achieve this we will multiply equation (2) by 3

(3)

3x +21y = 45
3x + 4y = 11
17y = 34

y=2

3x + 4y = 11
3x + 8 = 11
3x = 11 – 8
3x = 3

x=1

## Hence the solutions are :

x = 1 and y = 2

14
Example 2 Solve the equations

## 3x + 4y =26 ……. (1)

and 4 x − 3y = 18 ……. (2)

## To obtain the same coefficient of x, equation (1) is multiplied by 4

and equation (2) by 3

## 12x + 16y = 104 ……. (3)

12x − 9 y = 54 ……. (4)
25y = 50 y=2

3x + 8 = 26
3x = 26 − 8
3x = 18 x=6

## Hence the solution is: x = 6 and y = 2

Exercise 3
Solve the following simultaneous equations

1. 5x + 7 y = 29 2. 5x − y = 17
x + 2y = 7 4 x + 3y = 6

3. 5x + y = 22 4. 3x − 4 y = 30
2 x − 5y = 25 4x + 5y = 9

5. 6 x − 5 y = 11 6. 10 x + 3y = −24
4 x + 3y = 1 5x − 4 y = −23

7. x + 2 y = 10 8. 4 x = −5 y − 8
3x = 5 y − 3 6 x = 2 y + 26

9. 2 x + 3y = 2 10. 12 x − 3y = 1
8x − 9 y = 1 4x + 6 y = 5

15
MULTIPYING BRACKETS

(a+b)(c+d)

## If we now multiple each individual term of the first bracket by the

second bracket then
a(c+d) + b(c+d)
ac+ad +bc +bd

## Similarly (2x+3y)(4x+5y) = 2x(4x+5y) + 3y(4x+5y)

8x2 + 10xy +12xy + 15y2
8x2 + 22xy + 15y2

## And (x + y)2 = (x+y)(x+y)

x(x+y) + y(x+y)
x2 +2xy + y2

Expanding (3x − 4 y ) will become the first term squared, plus twice
2

the product of the first and second terms, plus the second term
squared.

So (3x − 4 y ) 2 = 9 x 2 − 24 xy + 16 y 2

Exercise 4

## 3. 10(2x + 7 y ) − 3(57 − 2x ) 4. 5(a 2 + 4b 2 ) − 3(3a 2 − 6b 2 )

5. (x + 2 )(x + 3) 6. (2 x + 3)(3x − 5)

7. (2x + 3y ) 8. (2x − 3y )
2 2

## 9. (2 x + 3y )(2 x − 3y ) 10. (3x + 5)(2 x − 3) + (5x − 3)(3x + 4 )

16
Factorising Quadratic Functions

## And the general quadratic equation is ax 2 + bx + c

Then if a = 1 x 2 + (m + n ) + mn = x 2 + bx + c

So b = m + n and c = mn

Example 1 Factorise x 2 + 5x + 6

## As 2×3= 6 and 2+3=5

x 2 + 5x + 6 = (x + 2)(x + 3)
Example 2 Factorise x 2 + 2 x − 150

As − 3 × +5 = −15 and − 3 + (+ 5) = +2

x 2 + 2 x − 15 = (x − 3)(x + 5)

Example 3 Factorise 2x 2 + 7 x + 6

As 3 × 2 = 6 and 2x × 2 = 4x and x × 3 = 3x

Giving 4x+3x=7x

2 x 2 + 7 x + 6 = (2 x + 3)(x + 2 )

Example 4 Factorise 3x 2 − 4 x − 15

## As 5 × −3 = −15 and x × 5 = 5x and 3x × −3 = −9 x

Giving 5x + ( −9 x ) = −4 x

3x 2 − 4x − 15 = (3x + 5)(x − 3)

17
Exercise 5 Factorise the following quadratic functions

1) x 2 + 7 x + 12 2) x 2 + 2 x − 15

3) x 2 − 3x − 28 4) x 2 − 11x + 28

5) x 2 − 15x + 56 6) 30 − 11x + x 2

7) 12 + 4m − m 2 8) 20 − a − a 2

9) 2 x 2 + 5x + 2 10) 3x 2 + 13x + 14

## 11) 3x 2 − 13x − 10 ` 12) 6 x 2 + 11x + 4

18
Solution of Quadratic Equations

## Method one – Factorisation

Example 1 Solve x 2 + 5x − 14 = 0

If x 2 + 5x − 14 = 0 then (x − 2)(x + 7 ) = 0
Therefore x − 2 = 0 and x+7=0

So x = 2 and x = −7

Example 2 5x 2 − 23x − 10 = 0

(5x + 2)(x − 5) = 0
5x + 2 = 0 and x − 5 = 0

2
x = − or − 0 ⋅ 5 and x = 5
5

## Exercise 6 Solve the following quadratic equations by factorisation

1) x 2 − 4x = 0 2) x2 − 4 = 0

3) 25x 2 − 16 = 0 4) x 2 + 5x = 0

5) x 2 − 7 x + 10 = 0 6) x 2 − x − 12 = 0

7) x 2 − 11x + 28 = 0 8) x 2 − 11x + 30 = 0

9) x 2 + 12 x + 35 = 0 10) x 2 − 63 = 2 x

## 11) 2 x 2 − 11x + 5 = 0 12) 5x 2 − 23x − 10 = 0

19
Solution of Quadratic Equations by Formula

## Given that the general form of a quadratic equation is

ax 2 + bx + c = 0

− b ± b 2 − 4ac
Then x=
2a

Example 1 Solve 3 x 2
+ 2 x − 8 = 0 using the quadratic
formula

Comparing 3x 2 + 2 x − 8 = 0 with ax 2 + bx + c = 0

Therefore a = 3 , b = 2 and c = −8

− 2 ± 2 2 − 4 × 3 × −8
So x=
2×3

− 2 ± 4 + 96
x=
6

− 2 ± 10 4
x= x= and x = 2
6 3

Example 2 Solve 2 x 2 − 9 x − 7 = 0

a = 2 , b = −9 and c = −7

− (− 9 ) ± (− 9) − 4 × 2 × (− 7 )
2

So x=
2× 2

9 ± 81 + 56 9 ± 137
x= x=
4 4

x = 5 ⋅ 18 and x = −0 ⋅ 68

20
Exercise 7 Solve the following quadratic equations by formula

1) 4 x 2 − 3x − 2 = 0 2) x2 − x −1= 0

3) 3x 2 + 7 x − 5 = 0 4) 7 x 2 + 8x − 2 = 0

5) 5x 2 − 4 x − 1 = 0 6) 2x 2 − 7 x = 3

7) x (x + 4 ) + 2 x (x + 3 = 5) 8) 5x (x + 1) − 2 x (2 x − 1) = 20

2 3 x+2 5
9) + =5 10) − =4
x + 2 x +1 3 x+2

3x − 5 x 2 − 2
11) = 12) x (x + 5) = 66
4 x

12 1
12) (2x − 3) 2
= 13 14) − =2
x+2 x

21
Indices

Laws of indices

x m × x n = x m+n

x m ÷ x n = x m+n

(x )m n
= x mn

x0 =1

x1 = x

1
x −m =
xm
1
m
x = xm
m
m
x =xn n

## Examples Simplify the following

3
x2 × x 2 1
2 1 5
1. = x × x ×−2
3 2
+ −2=−
x2 3 2 6
5

=x 6

3
⎛ 1⎞
2

x ×⎜x2 ⎟
5

⎝ ⎠
2 1 3
2 1 3 51
2. 3
= x5 × x8 × x4 + + =
− 5 8 4 40
x 4

51

= x 40

22
Exercise 8

## Without a calculator find the numerical value of the following

1 3 1

1) 5 ×5 ×5
2 2 2
2) 4÷4 2

1 1

3) 8 3
4) 64 6

2 3

5) 8 3
6) 25 2

3
⎛ 14 ⎞ 1
7) ⎜16 ⎟ 8) 3
⎝ ⎠ 9

2

1

⎛1⎞ 2
9) ⎜ ⎟ 10) 16 0⋅5
⎝ 4⎠

(4 )
1
−3 2
11) 36 −0⋅5 12)

−3
⎛ 1 ⎞
5

⎛ 1 ⎞2 ⎜ ⎟
13) ⎜ ⎟ 14)
⎝ 4⎠ ⎜ 2⎟1

⎝ 16 ⎠
1

1 ⎛9⎞ 2
15) 16) ⎜ ⎟
( 3) −2
⎝ 4⎠

23
Exercise 9 Simplify the following expressions, expressing each as
a single power.

1) x 2) 5
x4

1 1
3) 4)
x 3
x4

1
5) x −3 6) 4
x −0⋅3

( )
2
2
7) 3
−x 8) x 3

3

( x) ⎛ 1 ⎞
2 4
9) 3
10) ⎜3 4 ⎟
⎝ x ⎠

x 3
x −3
11) 12)
x × x
2 2
3
x
5 −3

x 3
x ×x 2 2
13) 3
14) 1

x 2
x 2

3 5 3
− −
x 4
x2 × x 2
15) 5
16) 7
− −
x 2
x 2
× x2
3
⎛ 12 ⎞
⎜x ⎟
17) ⎝ ⎠ 18)
x
(x )
1
3 2 x3

19)
4
x3
20)
( x)4
3

x x

4
x2 3
x × x3
21) 22) 5
7
x −2 x2

24